PERFORMANCE MEASUREMENT IN PRODUCTION COMPANY AS A SOURCE OF COMPETITIVE ADVANTAGE - Bešlić, Ivana; Bešlić, Dragana (Economics of Agriculture, 2010)
In the modern business environment efficiently and effectively manage the production company means defining an adequate system of measuring the financial and nonfinancial performance and acceptance of TQM concepts. Based on the concept of TQM and performance measurement in the field of total quality management, ensures competitive advantage of many manufacturing companies that follow the strategy of cost reduction, including a leading food company "Carnex" a.d. from Vrbas.